Efforts to Overcome Learning Problems through Eclective Counceling with Attending Behavior - Euis Haryani (EduResearch Mitra Inovasi, 2019)
Difficulties in student learning are indicated by the existence of certain obstacles to achieving learning outcomes and can be psychological, sociological, or physiological so that in the end it can cause the achievement of learning that is achieved under the proper level. Student learning difficulties include broad terms, including: (a) learning disorder; (b) learning dysfunction; (c) underachiever; (d) slow learner, and (e) learning disabilities. The problems examined in this study are in the form of counseling guidance services with elective therapy on attending behavior to overcome the learning problems of class IX-C students at SMP Negeri 108 Jakarta. The objectives of this study are: (a) To find out the effectiveness of the applied effective counseling model with attending behavior to overcome the learning problems of Class IX-C students at SMP Negeri 108 Jakarta, b) To find out the steps teachers must take in overcoming student learning problems through an effective counseling model with attending behavior, c) To find out the factors that cause problems that arise in class IX-C students' learning at SMP Negeri 108 Jakarta. This study uses a counseling guidance research service, carried out consisting of five stages namely case identification, problem identification, diagnosis, prognosis, and remedial or referral. The study period was three months from August to October 2018. The research subjects were Class IX-C students in 108 State Junior High School Jakarta 2018-2019 Academic Year on the subject of learning problems, in the odd semester with 5 students. The data obtained in the form of case investigations. Based on the results of the study, it can be concluded that by using an effective therapeutic technique with attending behavior in class IX-C students of SMP Negeri 108 Jakarta there are significant changes in efforts to overcome the learning problems that arise that are traumatic, extraordinary anxiety, unstable soul, and emotional, with categories of values ​​A and B.